ISLAM JAWA DAN PEACEFUL ISLAM SEBAGAI KONTRA RADIKALISME ISLAM DI PEDALAMAN RIAU, SUMATERA KONTEMPORER - Rubaidi, Rubaidi Rubaidi (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
This article is the result of research on the locality of Islam in Indonesia post-reformation, focusing on the rural areas of Riau, Sumatra. The study examines the dynamics of local Islam in three regencies, namely Siak, Pelalawan, and Rokan Hulu, in the province of Riau, uncovering various interesting phenomena. The Riau Malay Islam, which has deep historical roots influenced by Sufism, has developed a pattern and character of peaceful Islam. This peaceful Islam character is shaped through the acculturation of local traditions and culture. At a glance, this peaceful Islam seems to be a collective identity of the Riau Malay Muslims that is unchanging. However, this is not the case. Post-reformation Islam in Riau has undergone dynamic changes. The rise of radical Islamic ideologies promoted by several radical Islamic organizations has led to a shift in the mindset of the Malay Muslims from moderate and peaceful to more radical. Amidst this shift in Islamic thought in modern Riau Malay, networks of Javanese Muslims from various pesantren in Java affiliated with the Nahdlatul Ulama (NU) organization have been promoting the spirit of Javanese Islam, which is peaceful, akin to the Malay Islam inherited from their ancestors. In this open social structure, each actor plays a role in interpreting Islam within the mentioned social structure.